Contradictions and dilemmas in development of Hungarian food chain - Sarudi, Csaba; Lakner, Zoltán (Acta Agraria Kaposváriensis, 2003)
The globalisation and the European integration means new possibilities and threats for Hungarian agriculture and food production. The adaptation to the current processes on the world market of food and agricultural products needs the re-consideration of the development strategy of Hungarian food production. The utilisation of the Hungarian agro-ecological potential is decreasing. The production structure is rather rigid, giving only a limited possibility to the increase of value-added content of products. The strategy of product differentiation is a necessary precondition to increase the competitiveness and the price level of Hungarian products on the world market. The Hungarian experiences emphasise the importance of the human factor in the market adaptation. The concentration is a general process in agribusiness. The only possibility of the survival of small- and middle-scale economic entities in agriculture and food industry is cooperation. A specific problem is the concentration in domestic trade. The defence of interests of agricultural and food industrial enterprises should be increased by more rigorous application of the competition law.
Keywords: channel management; competitiveness; strategy; value chain